Association Between Self-Esteem and Happiness Among Adolescents in Malaysia: The Mediating Role of Motivation - Yap, Chin Choo *; Rohaiza, M. S.; Sum, X. Y.; Tan, S. A.; Yee, K. W. (Sage, 2021)
Adolescence is the developmental process of becoming an adult. This journey of physical and psychological maturation is filled with challenges and hormonal chaos, and teenagers experience unhappiness at times. From a psychological perspective, this study aimed to examine the association between motivation, self-esteem and happiness; and to explore the mediating role of motivation in the association between self-esteem and happiness among adolescents in Malaysia. 480 secondary school students were recruited using a multistage cluster sampling method and answered the Malay versions of the Subjective Happiness, Brief Motivation and Rosenberg Self-esteem scales. Both self-esteem and motivation were found positively correlated to happiness. The hypothetical mediating role of motivation on the association between self-esteem and happiness was also supported, indicating that individuals with higher self-esteem have higher motivation which may result in greater happiness. Since the direct association between self-esteem and happiness remained significant, a partial mediation of adolescents’ motivation between self-esteem and happiness is indicated. The results showed that perceived self-esteem plays a role in predicting happiness and the presence of motivation enhances happiness, providing an insight to nurture happier adolescents for parents and educators in Malaysia.